Opportunities for Therapeutic Intervention During Machine Perfusion - Karimian, Negin (Curr Transplant Rep, 2017)
PURPOSE OF REVIEW: There is a vast discrepancy between the number of patients waiting for organ transplantation and the available donor organs. Ex vivo machine perfusion (MP) has emerged in an effort to expand the donor pool, by improving organ preservation, providing diagnostic information, and more recently, acting as a platform for organ improvement. This article reviews the current status of MP with a focus on its role in organ preconditioning and therapeutic interventions prior to transplantation. RECENT FINDINGS: MP has allowed longer organ preservation compared to conventional static cold storage and allowed the use of organs that might otherwise have been discarded. Moreover, experimental studies have investigated the role of MP in reducing ischemia reperfusion injury of lungs, kidneys and livers by applying mesenchymal stem cells (MSCs), anti-inflammatory agents, cytotopic anticoagulants, and defatting cocktails. SUMMARY: MP has opened a new era in the field of organ transplantation and tissue medication.